BIMBINGAN KELOMPOK TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN ADVERSITY QUOTIENT MAHASISWA TINGKAT AKHIR - Faijah; Rizki Novirson; Nana Meily Nurdiansyah (JIEGC Journal of Islamic Education Guidance and Counselling, 2024)
This study aims to determine the effectiveness of problem solving technique group guidance in improving the adversity quotient ability of final year students. This study uses a quantitative approach with a quasi-experimental non-equivalent pre-test post-test control group design. The research was conducted on 20 final year students at the Daarul Qur'an Institute Jakarta by purposive sampling. The research instrument uses an adversity quotient inventory that has met the requirements for validity and reliability. This study supports Stoltz's theory that explains the adversity quotient, which is a series of tools that have a scientific basis to improve an individual's response to adversity. The results of the study were obtained that there was a significant increase in adversity quotient before and after group guidance with problem solving techniques, with Z calculated as -2, 807 and Asymp. Sig (2 tailed) is 0.005.